IMPLEMENTASI ADAPTASI TEKNOLOGI DALAM PROGRAM KAMPUS MENGAJAR 8 DI SD NEGERI 12/I TERUSAN - Dzulqadri, Abraar; Yantoro; Alirmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the planning, implementation, and impact of technology adaptation in the Kampus Mengajar 8 program at SD Negeri 12/I Terusan. The research employs a qualitative approach with a phenomenological design. Data were collected through interviews, observations, and document analysis. The research subjects include Kampus Mengajar students, the school principal, teachers, and students. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques. Data validity was ensured through source triangulation. The findings indicate that, in the planning stage, Kampus Mengajar students first conducted observations at the school. The results of these observations served as the basis for designing technology adaptation activities, which were then incorporated into the Collaborative Action Plan (RAK) and agreed upon with the school. The implementation stage of technology adaptation was divided into two main activities. First, Kampus Mengajar students conducted training sessions on creating interactive teaching media using Canva for teachers, aiming to enhance their skills in utilizing technology as a teaching aid. Second, technology was integrated into classroom activities for students, such as using Wordwall and screening educational films to make learning more interactive and engaging. The impact of this technology adaptation was evident among both teachers and students. For teachers, the program helped improve their understanding of technology and boosted their confidence in using it in teaching. Meanwhile, for students, technology adaptation increased their enthusiasm for learning and helped them better understand the subject matter